EFEKTIFITAS MENDENGARKAN MUROTTAL AL-QURAN TERHADAP SKOR HALUSINASI PADA PASIEN HALUSINASI PENDENGARAN - Armona " Sari; Jumaini " "; Sri " Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this research is to determine effectiveness of murottal Al-Quran’s therapy toward score of hallucination in patient with auditory of hallucination. The method of this research was quasy experiment with pretest-posttest design with control group. The research was conducted in psychiatric hospital Tampan Riau Province with sampel of 34 patients with risk of violence behaviour which divided into 17 people as experimental group and 17 people as control group and the sampling method was purposive sampling. Instruments of this research used score hallucination questionnaire which has been tested for the validity and reliability. Experimental group was trained with murottal Al-Quran’s therapy for 6 times for six days, meanwhile control group were not. The analysis that used  in this research were univariate and bivariate analysis used wilcoxon test and mann-whitney. The result of the research showed that there was a significant decrease score of hallucination after given intervention murottal Al-Quran’s therapy between experimental group with p value 0,01 (p < 0,05). In conclusion murottal Al-Quran’s therapy is effective to decrease score of hallucination. The result of this research recommended to be applied for nursing intervention to patient’s hallucination.   Keyword : Hallucination, murottal Al-Quran’s therapy, score of hallucination.